Effects of high-intensity interval training on cardiopulmonary function and quality of life in post-PCI or CABG patients with coronary heart disease: a meta-analysis - Guizhen Hong; Fei Liu (Journal of Cardiothoracic Surgery)
Abstract Background High-intensity interval training (HIIT) has emerged as a potential cardiac rehabilitation strategy for coronary heart disease (CHD) post-surgery, but its efficacy compared to moderate-intensity continuous training (MICT) remains uncertain. Aim This meta-analysis aimed to evaluate the effects of HIIT on cardiopulmonary function and quality of life in CHD patients post-PCI or CABG in comparison with MICT. Methods We systematically reviewed randomized controlled trials from PMID, Cochrane, Embase, Wanfang, and China National Knowledge Infrastructure (CNKI) databases comparing HIIT with MICT in CHD patients. Data on peak oxygen uptake (VO2peak), left ventricular ejection function (LVEF), heart rates, and quality of life were extracted and analyzed using random—or fixed-effects models based on heterogeneity. Results HIIT significantly improved VO2peak by 1.678 mL/kg/min (95%CI = 1.082–2.275), increased LVEF by 2.831% (95%CI = 1.124–4.538), enhanced peak HR by 6.717 beats/min (95%CI = 5.111–8.323) compared to MICT. Resting HR did not differ significantly between groups. Quality of life (SMD = 0.132, 95%CI = 0.051–0.213, P = 0.001) was significantly elevated by HIIT, particularly in the physical domain. Subgroup analyses showed consistent benefits of HIIT across exercise durations and times. Conclusion HIIT effectively enhances cardiopulmonary function and quality of life in CHD post-surgery. HIIT may be a time-efficient alternative to MICT in cardiac rehabilitation programs. However, publication bias and high heterogeneity warrant caution in interpreting these results, indicating a need for further research.